A Giant Metastatic Inguinal Lymph Node from Melanoma - Bertheuil, N. (Springer India, 2012)
A 49-year-old woman was admitted to our institution with a giant necrotizing and ulcerative inguinal mass that measured 17 × 11 centimeters. She had a history of dorsal ulcerated nodular melanoma with a Breslow thickness to 10 mm, clark’s level was 4 and an mitotic activity of 1 mitosis per 40 high-power fields. She was operated in emergency for an ilioinguinal dissection, then 15 days later, a secondary coverage by Taylor’s flap. The pathological examination found a melanoma metastasis. She is alive at fourteen months after the operation.